Systemic Immunosuppression for Limbal Allograft and Allogenic Limbal Epithelial Cell Transplantation - Serna-Ojeda, Juan Carlos (Med Hypothesis Discov Innov Ophthalmol, 2020)
Bilateral limbal stem cell deficiency (LSCD) treatment requires the need to obtain allogenic limbal tissue for transplantation. Outcomes of different surgical techniques depend on multiple factors, including the underlying etiology, ocular surface, eyelid status and used surgical intervention. Some of the management options for bilateral LSCD include cadaveric, living related or living non-related conjunctival limbal allograft (CLAL), keratolimbal allograft (KLAL), allogenic cultured limbal epithelial transplantation (CLET) and allogenic simple limbal epithelial transplantation (SLET). Systemic immunosuppressive therapy plays a pivotal role in survival of transplanted tissue. The present review focuses on different systemic immunosuppression protocols for limbal allograft and allogenic limbal epithelial cell transplantation, with specific emphasis on different surgical techniques and their outcomes. We included all reports with details of different systemic immunosuppression protocols for limbal allograft and allogenic limbal epithelial cell transplantation. Oral cyclosporine A at different doses is the most commonly used immunosuppressive agent in limbal allograft and allogenic limbal epithelial cell transplantation. However, different studies using oral mycophenolate mofetil and tacrolimus also reported good results. In conclusion, systemic immunosuppression protocols for limbal allograft and allogenic limbal epithelial cell transplantation are not standardized. Further studies regarding different surgical techniques should assess outcomes and adverse effects of such protocols.